L’arrière-plan sociologique du champ sémantique de l’étranger dans le Pentateuque - Varo, Francisco (Revue des sciences philosophiques et théologiques, 2018)
The semantic value of the terms designating foreigners, displaced persons and immigrants in biblical texts evolves diachronically and depends on the historical contingencies of judahite society. The juridical treatment of these people, or even the popular perception of them, also changes over time. This study intends to clarify the relationship between these terms' social background and biblical meaning in each stage of the process of the Pentateuch's composition.